Assessment of Pleural Effusion by Means of Imaging Modalities - Kumari, Swati; Jaseemudheen, M.M. (Journal of Health and Allied Sciences NU, 2022)
Pleural effusion is the fluid collection in the pleural cavity between the parietal and visceral pleura. It is caused by parenchymal diseases such as inflammatory disorders or infection. Pleural effusion can be diagnosed using imaging modalities such as X-ray, computed tomography (CT) scan, ultrasound, and magnetic resonance imaging (MRI).MRI is rarely performed to investigate pleural effusion due to motion artifacts and has a poor spatial resolution. Benign and malignant pleural effusion can be diagnosed using an X-ray, CT scan, or ultrasound. Pleural effusion volume can be measured by using ultrasound. This article reviews the feasibility of investigating pleural effusion and fluid drainage in medical imaging and compares to find the best modality for its diagnosis.Description: This article reports the possible options to detect pleural effusion in medical imaging and compares them to find the best modality for its diagnosis.
Keywords: pleural effusion; pleural effusion volume; contrast-enhanced computed tomography